2011
DOI: 10.1590/s1413-86702011000200007
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxins, colonization factors, serotypes and antimicrobial resistance of enterotoxigenic Escherichia coli (ETEC) strains isolated from hospitalized children with diarrhea in Bolivia

Abstract: Enterotoxigenic Escherichia coli (ETEC) is recognized as the main cause of bacterial diarrhoea among children in Asia, Africa and Latin America but less investigated in Bolivia. Objective: To determine the relation between enterotoxins, CFs and serotypes as well as the antimicrobial resistance patterns in a set of ETEC isolates collected from hospitalized children with acute diarrhea. In the present study we characterized 43 ETEC strains isolated from 2002 to 2006 from hospitalized children (0-5 years) with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
12
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
4
12
1
Order By: Relevance
“…However, although ST and LT/ST ETEC strains were significantly more frequent in diarrhea cases in this study, they did not cause symptoms of greater severity than those seen with LT-only isolates, supporting the notion that LT-only ETEC strains may cause severe diarrhea. This finding is consistent with data from recent studies reporting an increased prevalence of LT ETEC strains causing severe symptoms (16,37). Analysis of the presence of putative virulence factors clyA, eatA, east-1, tibC, tia, and leoA in ETEC strains isolated from children with and without diarrhea did not reveal any association among these factors in ETEC and diarrhea.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, although ST and LT/ST ETEC strains were significantly more frequent in diarrhea cases in this study, they did not cause symptoms of greater severity than those seen with LT-only isolates, supporting the notion that LT-only ETEC strains may cause severe diarrhea. This finding is consistent with data from recent studies reporting an increased prevalence of LT ETEC strains causing severe symptoms (16,37). Analysis of the presence of putative virulence factors clyA, eatA, east-1, tibC, tia, and leoA in ETEC strains isolated from children with and without diarrhea did not reveal any association among these factors in ETEC and diarrhea.…”
Section: Discussionsupporting
confidence: 92%
“…However, variations in toxin profiles were observed from year to year. Different studies in Latin America have shown differences in the predominant toxin type; for instance, LT/ST ETEC strains were found to be most prevalent in Peru (19), ST-only ETEC strains in Brazil (20) and LT ETEC strains in Argentina (23), in Nicaragua (21), and in a previous report from Bolivia (16). A similar trend has been observed in Bangladesh, where different toxin profiles have predominated over the years (24)(25)(26).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It is well known that the production of CFAs can be variable due to genetic defects in the genes required for expression (27) and the composition of bacterial growth media and growth conditions; this is particularly true for CS21, which requires unique growth conditions (36). A number of studies have reported that genotypic methods offer certain advantages over phenotypic methods (18,37). These studies suggest that there is increased sensitivity and specificity of CFA detection using molecular tools.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of antibiotic resistance showed that 67% (n = 29/43) of the enterotoxigenic E. coli strains were resistant to one or several of the antimicrobial agents tested. The presence of colonization factors was associated with antibiotic resistance [6]. Cephalosporinase producing E. coli has recently been detected in meat and animals [7].…”
mentioning
confidence: 99%